Mining the social web - Russell, Matthew A. (Computer scientist) (O'Reilly, 2011)
Facebook, Twitter, and LinkedIn generate a tremendous amount of valuable social data, but how can you find out who's making connections with social media, what they're talking about, or where they're located? This book shows you how to answer these questions and more. Each chapter introduces techniques for mining data in different areas of the social web, including blogs and email.